Temporal association of sNfL and gad‐enhancing lesions in multiple sclerosis - Rosso, Mattia; Gonzalez, Cindy T.; Healy, Brian C.; Saxena, Shrishti; Paul, Anu; Bjornevik, Kjetil; Kuhle, Jens; Benkert, Pascal; Leppert, David; Guttmann, Charles; Bakshi, Rohit; Weiner, Howard L.; et al. (Annals of clinical and translational neurology, 2020)
Objective Multiple sclerosis (MS) is an autoimmune demyelinating disorder, which is characterized by relapses and remissions. Serum neurofilament light chain (sNfL) is an emerging biomarker of disease activity but its clinical use is still limited. In this study, we aim to characterize the temporal association between sNfL and new clinical relapses and new gadolinium‐enhancing (Gd+) lesions. Methods Annual sNfL levels were measured with a single‐molecule array (SIMOA) assay in 94 patients with MS enrolled in the Comprehensive Longitudinal Investigation of Multiple Sclerosis at the Brigham and Women’s Hospital (CLIMB) study. We used a multivariable linear mixed‐effects model to test the temporal association of sNfL with clinical relapses and/or new Gd+ lesions. We adjusted this model for age, disease duration, sex, and disease‐modifying therapies (DMTs) use. Results In the 3 months after a Gd+ lesion, we observed an average 35% elevation in sNfL (P < 0.0001) compared to remission samples. We also observed an average 32.3% elevation in sNfL at the time of or prior to a Gd+ lesion (P = 0.002) compared to remission. We observed a significant elevation in sNfL after a clinical relapse only when associated with a Gd+ lesion. Interpretation Our findings support sNfL as a marker of clinical relapses and Gd+ lesions. sNfL peaks in a 3‐month window around Gd+ lesions. sNfL shows promise as a biomarker of neurological inflammation and possibly of simultaneous Gd+ lesions during a clinical relapse.